Research on Corrosion Protection of TETA-Modified Li–Al LDHs for AZ31 Magnesium Alloy in Simulated Seawater - Sifan Tu; Liyan Wang; Sixu Wang; Haoran Chen; Qian Huang; Ning Hou; Zhiyuan Feng; Guozhe Meng (Metals)
Magnesium alloys are lightweight metals but suffer from high corrosion susceptibility due to their chemical reactivity, limiting their large-scale applications. To enhance corrosion resistance, this work combines Li–Al layered double hydroxides (LDHs) with triethylenetetramine (TETA) inhibitors to form an efficient corrosion protection system. Electrochemical tests, SEM, FT-IR, XPS, and 3D depth-of-field microscopy were employed to evaluate TETA-modified Li–Al LDH coatings at varying concentrations. Among them, the Li–Al LDHs without the addition of a TETA corrosion inhibitor decreased significantly at |Z|0.01 Hz after immersion for 4 h. However, the Li–Al LDHs coating of 23.5 mM TETA experienced a sudden drop at |Z|0.01 Hz after holding for about 60 h, and the Li–Al LDHs coating of 70.5 mM TETA also experienced a sudden drop at |Z|0.01 Hz after holding for about 132 h. By contrast, at the optimal concentration (47 mM), after 24 h of immersion, the maximum |Z|0.01 Hz reached 7.56 × 105 Ω∙cm2—three orders of magnitude higher than pure Li–Al LDH coated AZ31 (2.55 × 102 Ω∙cm2). After 300 h of immersion, the low-frequency impedance remained above 105 Ω∙cm2, demonstrating superior long-term protection. TETA modification significantly improved the durability of Li–Al LDHs coatings, addressing the short-term protection limitation of standalone Li–Al LDHs. Li–Al LDHs themselves have a layered structure and effectively capture corrosive Cl− ions in the environment through ion exchange capacity, reducing the corrosion of the interface. Furthermore, TETA exhibits strong adsorption on Li–Al LDHs layers, particularly at coating defects, enabling rapid barrier formation. This inorganic–organic hybrid design achieves defect compensation and enhanced protective barriers.